Tapas in the Rg Veda - Murdock, Anthony L. (My University, 1983)
It is my contention in this thesis that the term tapas means heat, and heat only, in the Rig Veda. Many reputable scholars have suggested that tapas refers to asceticism in several instances in the RV. I propose that these suggestions are in fact unnecessary. To determine the exact meaning of tapas in its many occurrences in the RV, I have given primary attention to those contexts (i.e. hymns) in which the meaning of tapas is absolutely unambiguous. I then proceed with this meaning in mind to more ambiguous instances. In those instances where the meaning of tapas is unambiguous it always refers to some kind of heat, and never to asceticism. Since there are unambiguous cases where tapas means heat in the RV, and there are no unambiguous instances in the RV where tapas means asceticism, it only seems natural to assume that tapas means heat in all instances. The various occurrences of tapas as heat are organized in a new system of contextual classifications to demonstrate that tapas as heat still has a variety of functions and usages in the RV.
In conclusion, I suggest that heat works very well as a translation for tapas in the RV. While it is of course possible that other meanings of tapas were acceptable to Vedic man, it seems to me that we must await support from the RV itself before accepting any meaning beyond that of heat, the only meaning which is in fact documented in the RV. This approach to understanding tapas in the RV (i.e. contextual analysis) may help to solve some of the problems modern scholars have faced when attempting to translate a term such as tapas in the RV.
Keywords: tapas; Religion; Religion